2016
DOI: 10.1002/stem.2308
|View full text |Cite|
|
Sign up to set email alerts
|

miR-126-3p Promotes Matrix-Dependent Perivascular Cell Attachment, Migration and Intercellular Interaction

Abstract: microRNAs (miRNAs) can regulate the interplay between perivascular cells (PVC) and endothelial cells (EC) during angiogenesis, but the relevant PVC-specific miRNAs are not yet defined. Here, we identified miR-126-3p and miR-146a to be exclusively upregulated in PVC upon interaction with EC, determined their influence on the PVC phenotype and elucidate their molecular mechanisms of action. Specifically the increase of miR-126-3p strongly promoted the motility of PVC on the basement membrane-like composite and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
5
18
0
Order By: Relevance
“…The current study demonstrated that Tlr3 is upregulated in brain stem of ISIAH rats. Earlier it was shown that TLR3 expression may be stimulated to modulate cell-cell and cell-matrix contacts of perivascular cells playing a role in angiogenesis and blood vessels permeability [53].…”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrated that Tlr3 is upregulated in brain stem of ISIAH rats. Earlier it was shown that TLR3 expression may be stimulated to modulate cell-cell and cell-matrix contacts of perivascular cells playing a role in angiogenesis and blood vessels permeability [53].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of miRNAs, such as miR-223, miR-155, and miR-21, were found to be upregulated in mature osteoblasts, influencing osteoclastogenesis, and regulating the production of extracellular matrix and, thus, bone mass (see [Lian et al, 2012] and [Taipaleenmaki et al, 2012] for review). miR-126 is a well-studied molecule which has been chiefly associated with regulation of angiogenesis and vascular integrity [Fish et al, 2008;Wang et al, 2008;Zhang et al, 2013;Chen et al, 2016;Pitzler et al, 2016]. Interestingly, the data from our laboratory show that miR-126 has anti-angiogenic properties in peripheral blood endothelial progenitor cells [Goerke et al, 2015].…”
Section: Discussion Mirnas In Osteoblast Biologymentioning
confidence: 85%
“…miR‐126 is a well‐studied molecule which has been chiefly associated with regulation of angiogenesis and vascular integrity [Fish et al, ; Wang et al, ; Zhang et al, ; Chen et al, ; Pitzler et al, ]. Interestingly, the data from our laboratory show that miR‐126 has anti‐angiogenic properties in peripheral blood endothelial progenitor cells [Goerke et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of hsa-mir-126-3p can promote cell proliferation and migration by activating PI3K/AKT signaling pathway (29). Hsa-mir-126-3p is reported as a novel regulator of PVC-mediated vessel stability during tumor angiogenesis (30). The expression of hsa-mir-126-3p is increased in patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%